ANALISIS PENANGANAN PENERIMAAN TANDAN BUAH SEGAR PADA PT. BIO NUSANTARA TEKNOLOGI DI KECAMATAN PONDOK KELAPA KABUPATEN BENGKULU TENGAH - Rizki, January; Nusril, Nusril; Asriani, Putri Suci (Jurnal AGRISEP, 2014)
This paper aimed to determine the handling system receiving TBS in PT.Bio Nusantara Teknologi to three supplier of partners supplier, plasma supplier and general supplier and how opportunities for improvement that can be done. This study used decriptive analysis and F test to examined wether there is discrimination in handling treatment and price of TBS among suppliers. The results showed that there are several steps that must be passed TBS suppliers to sell it to the POM: 1) taking a queue number, 2) The calling queue number, 3) Weighing, and 4) Sorting and loading and unloading. There was no difference in the treatment of the company against a third supplier, but the difference is the quality of fruit that would affect the price. The price difference was tested using the Tukey’s test or BNJ. From the results of the research sequence starting price of the highest rates of plasma suppliers, partners supplier and then general supplier.